Isolation of influenza A viruses from pigs in Ibadan,Nigeria (2009)
The authors investigated influenza virus types in pigs in Ibadan, a city in Oyo State, southwestern Nigeria. From April to June 2008, nasal swabs were collected from pigs at three locations in Ibadan. Influenza A viruses (four A [H1N1], two A [H3N2] and one A [H1N1]‐ A [H3N2] double reactant) were isolated from 7 of the 50 apparently healthy Landrace pigs tested. This study is the first documented isolation of swine influenza viruses in Nigeria and it reveals that different strains of influenza viruses co‐circulate in pigs in Ibadan. These pigs serve as reservoirs of different subtypes of influenza viruses and potential ‘mixing vessels’ in which genetic reassortment and the generation of future human pandemic strains could occur. These findings support the need for adequate and periodic surveillance among swine populations and pig handlers in Nigeria to detect circulating strains of influenza viruses. This would serve as an effective early warning system.